PERILAKU MEMILIH MAHASISWA PADA PEMILIHAN UMUM TAHUN 2014 DI LAMPUNG - Hertanto Hertanto (Jurnal Ilmiah Mimbar Demokrasi, 2015)
This study aims to: (1) identify trends in students in selecting candidates and political parties, (2) know the reasons students choose candidates and political parties, and (3) explain the factors that led to the student in choosing difficult. To explain the purpose of this study used a behavioral approach choosing (voting behavior). While the types of research using qualitative methods of data collection through interviews and open questionnaires. The results showed that (1) students tend to choose based nationalist political party, the PDI-P, the Democratic Party, and Gerindra. In selecting candidates for the legislature and the executive (the prospective governor/vice governor), students tend to prefer candidates who are well known and have an emotional attachment; (2) The reasons students choose a political party because he felt the presence of emotional closeness with the concerned parties or the candidates (candidates) are carried by the parties concerned. (3) Students assume the 2014 election had a lot of trouble to vote, because it is only 9.58% which assumes no difficulty in choosing. While the cause is considered to be the most difficult in choosing is non-technical factors such as too many candidates, the candidates are not known, ballots that are too big, and not accompanied by photographs candidates (DPRD).